Digital libraries for university theses: a case study of the library of the Ministry of Higher Education and Scientific Research in Syria (Damascus University Journal of arts and humanities sciences, 2025)
The prevalence of digital libraries has accelerated, their area has expanded and it necessary has become more emerge, especially in recent times,  which has made many different systems for digital libraries Under observation, ahead of many questions, whether about their effectiveness, their fulfillment of different requirements,  the extent of their competition between them in terms of their features, their prices, or the difference between their various terms, the scientific theses contained in libraries and produced by universities - which are considered an honest mirror that reflects the image of the university in any country, its progress, its development, or the imageof education and scientific research in it - is of great importance to the establishment of its own digital libraries; To contribute to the continuity and development of scientific research and reduce repetition, waste of effort, and time. This research presents the most important concepts of digital libraries, and their various systems. It studies the digital library system for theses in the Ministry of Education and Scientific Research in the Syrian Arab Republic
Keywords: Digital Libraries; Theses; Ministry of Higher Education and scientific research